POLA KOMUNIKASI PEDAGANG DAN PEMBELI DI PASAR TRADISIONAL: PERSPEKTIF JENDER DI PASAR SIDODADI KLECO SURAKARTA - Joko Sutarso (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2017)
The simply definition of market is meeting place between sellers and buyers. Market traditionalresponsible activity more than just economic, but also as a venue for social activities, culture, andcommunication. The purpose of this study were to determine the pattern of good communicationbetween merchants and between merchants and buyers, then also want to study how therelationship patterns of men and women at traders family. The method used an explanatoryqualitative, using the method of data collection is mainly on observations and interviews. Theresults of this study showed that there is a relatively equal division of labor and egalitarian in amerchant family; Patterns of communication between the merchant, or merchants with shoppersladen with the philosophy and values of brotherhood, mutual help, are not solely economicrelations.